IL-9 and Th9 cells in health and diseases—From tolerance to immunopathology - Li, Junhui; Chen, Shuqiu; Xiao, Xiang; Zhao, Yong; Ding, Wenjun; Li, Xian C. (Cytokine & growth factor reviews, 2017)
[Display omitted] •Th9 cells are a new T helper subset; they are induced by TGF-β and IL-4 and are characterized by producing IL-9.•IL-9 is a pleiotropic cytokine, exerting beneficial and deleterious effects in different models in vivo.•IL-9 and Th9 cells are promising targets for clinical interventions in various disease settings.•More studies are warranted in understanding of the fundamental biology of Th9 cells. CD4+ T cells have the capacity to differentiate into various T helper (Th) cell subsets after activation, and by acquiring distinct cytokine profiles and effector functions, they regulate the nature as well as the outcomes of immune responses. Th9 cells are a relatively new member in the Th cell family. The signature cytokine for Th9 cells is IL-9, a cytokine in the IL-2Rγc-chain family. Over the past few years, there has been an explosion of knowledge on the roles of Th9 cells in immunity and immunopathology, but the exact mechanisms in the control of Th9 cells remain poorly defined. This apparent paradox presents both challenges and opportunities. Here we review recent advances in our understanding of the fundamental biology of IL-9 and Th9 cells, highlighting the challenges and unanswered questions in the field. We also discuss potential opportunities in targeting Th9 cells for therapeutic purposes in the clinic.